2022
DOI: 10.1164/rccm.202112-2761oc
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Patients with Pulmonary Hypertension: A National Prospective Cohort Study

Abstract: Rationale Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is associated with pulmonary endothelial dysfunction. There are limited data available on the outcomes of coronavirus disease (COVID-19) in patients with pulmonary hypertension (PH), a disease characterized by pulmonary endothelial dysfunction. Objectives To describe characteristics and outcomes of patients with precapillary PH and COVID-19. Methods We prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 47 publications
4
26
1
2
Order By: Relevance
“…Farmakis et al reported a 3.6% incidence of COVID-19 in PH groups 1 and 4 patients in Greece, which was a little less than that in the general population [20]. Montani et al reported that 2.9% of PH patients with precapillary hypertension in France were diagnosed with COVID-19, a figure higher than the incidence in the general population [11]. While we observed our PAH/CTEPH patients for the 2 years of the pandemic, other authors collected data only in the early months of the pandemic, or before vaccines were rolled out.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Farmakis et al reported a 3.6% incidence of COVID-19 in PH groups 1 and 4 patients in Greece, which was a little less than that in the general population [20]. Montani et al reported that 2.9% of PH patients with precapillary hypertension in France were diagnosed with COVID-19, a figure higher than the incidence in the general population [11]. While we observed our PAH/CTEPH patients for the 2 years of the pandemic, other authors collected data only in the early months of the pandemic, or before vaccines were rolled out.…”
Section: Discussionmentioning
confidence: 96%
“…During the first months of the pandemic, there were reports from the United States and Europe of much higher mortality due to COVID-19 in patients with PAH and CTEPH compared to the general population [9,10]. Only one study has examined the impact of PH severity on COVID-19 outcome before vaccination [11]. A high mortality rate may be the consequence of a more severe course of COVID-19 in seriously ill PH patients, although limited diagnostic testing and control visits during the pandemic might have delayed PH diagnosis and early detection of disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Increased RV afterload can be secondary to pulmonary parenchymal abnormalities during acute infection, combined with macro- or micro-PVD as well as the negative inotropic, prothrombotic, and profibrotic effects of cytokine storm [ 119 121 ]. Additionally, patients with RV dysfunction and PH, in particular, experience worse clinical outcomes [ 117 , 122 ].…”
Section: Potential Long-term Effects Of Covid-19 On the Development O...mentioning
confidence: 99%
“…The largest study conducted comes from the French PH registry and included 211 patients with pre-capillary PH (among them 58.3% with a diagnosis of PAH) and a diagnosis of COVID-19 from February 2020 to April 2021 ( 9 ). In this prospective cohort, 32.2% of patients were hospitalized in a common ward, while an additional 27.5% of patients were hospitalized in intensive care unit (ICU); the median length of stay was 9 ( 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ) days. High-flow nasal cannula and corticosteroids were increasingly used after September 2020, while the proportion of patients receiving mechanical ventilation (11.1%) was similar between the two first waves of the pandemic.…”
Section: Introductionmentioning
confidence: 99%